The Teachers' Professional Development in Singapore and Malaysia: Experience for Vietnam - Bich, Truong Thi (VNU Journal of Science: Education Research, 2024)
The quality of education and the quality of a country's human resources depend greatly on its teachers. Therefore, training and fostering teachers play an important role in the development of the country. The article addresses some issues of two countries, Singapore and Malaysia, in teacher professional development. These are the issues: enrollment and training; recruitment and training; Rewarding, encouraging and honoring teachers. This article analyzes the strengths of these two countries in teacher training and development. In the context of fundamental and comprehensive reform of education in Vietnam, the reform of teacher training programs in the direction of professional development is being researched by teacher training institutions to find appropriate directions. The 21 st century teacher training model of Malaysia and Singapore is a valuable experience for us to learn and apply in building and developing teacher careers in Vietnam.